ОСОБИСТІСНО-ОРІЄНТОВАНИЙ ПІДХІД ДО УЧНІВ ОСНОВНОЇ ШКОЛИ ПРИ ПРОВЕДЕННІ ЗАНЯТЬ З РУЧНОЇ ХУДОЖНЬОЇ ПРАЦІ (Педагогіка вищої та середньої школи, 2003)
In the article the potential o flessons of labour training in realization of personally oriented approach to education of modern schoolboys is investigated. The author emphasizes expediency of use with this purpose of computertechnologies.